2014
DOI: 10.7314/apjcp.2014.15.17.7287
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Brief Physician Counselling Session on Improving Smoking Behaviour in the Workplace

Abstract: Background: Brief physician counselling has been shown to be effective in improving smokers' behaviour. If the counselling sessions can be given at the workplace, this would benefit a larger number of smokers. This study aimed to determine the effectiveness of a ten-minute physician counseling session at the workplace in improving smoking behaviour. Materials and Methods: This prospective randomised control trial was conducted on smokers in a factory. A total of 163 participants were recruited and randomised i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
(13 reference statements)
0
8
1
Order By: Relevance
“…Attending the 5A group counseling and reading the posters also helped to improve smoking-related knowledge and attitudes. Previous studies suggested the importance of 5A intervention and general education in improving knowledge and attitudes [15,16]. We did not find other smoking cessation efforts such as social media interventions or open lectures as being important predictors, perhaps due to the limited coverage (Table 3).…”
Section: Smoking-related Knowledge and Attitudescontrasting
confidence: 52%
See 2 more Smart Citations
“…Attending the 5A group counseling and reading the posters also helped to improve smoking-related knowledge and attitudes. Previous studies suggested the importance of 5A intervention and general education in improving knowledge and attitudes [15,16]. We did not find other smoking cessation efforts such as social media interventions or open lectures as being important predictors, perhaps due to the limited coverage (Table 3).…”
Section: Smoking-related Knowledge and Attitudescontrasting
confidence: 52%
“…Conducting smoking cessation interventions in the workplaces, including recruitment and regular follow-ups is necessary, given the high smoking rate among the workers; but also feasible as they work together and spend most of their daily time in their workplace [14]. Previous studies have suggested the efficacy of smoking cessation interventions in the workplace [15][16][17][18][19]. Several intervention approaches have shown to be effective for tobacco control including individual or group counselling, pharmacotherapy, and incentives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicated that health professionals are willing to participate in tobacco cessation activities (Binnal et al, 2012, Saba et al, 2014, Han et al, 2014. Nevertheless, lack of expertise and administrative barrier has been reported as main barriers in inclusion of tobacco control in the health care professional curriculum (Panda et al, 2013, Yadav et al, 2014.…”
Section: Effectiveness Of Tobacco Education For Pharmacy Students In mentioning
confidence: 99%
“…Due to the dramatic rate of smoking among the factory workers (8) and setting basic health interventions as the most favorable intervention to recognize the barriers of quitting smoking in the work settings and assess the effectiveness of the interventions (8), it was decided to select the automobile manufacturing company in Bam, Iran and the workers as the participant of the study in order to psychometrically evaluate the short form of situational temptations scale for smoke cessation among Iranian workers as the purpose of the current study.…”
Section: Introductionmentioning
confidence: 99%